Prevalence of major cardiometabolic diseases in the riverine populations from the interior of the State of Amazonas, Brazil - Paulo Lima de Azevedo; Silvia Regina Sampaio Freitas (Universidade Estadual de Maringá, 2018)
This study aimed to estimate the prevalence of major cardiometabolic diseases according to the sociodemographic characteristics and lifestyle in the riverine communities of the municipalities of Tefé and Santa Isabel do Rio Negro, State of Amazonas, Brazil. Descriptive tests and logistic regression models were used to estimate the effect of age, gender, marital status, education, smoking, alcohol consumption and sedentary lifestyle on the prevalence of cardiometabolic diseases in 552 adults aged from 18 to 78 years. The prevalence of hypertension, diabetes and obesity in Tefé and Santa Isabel do Rio Negro were respectively 28 / 30.7%; 28.2/ 8.9%; and 22.3 / 42%. In Tefé, married men, aged over 35 years, were more susceptible to the cardiometabolic diseases. In Santa Isabel do Rio Negro, smoking men aged over 35 with low education level were more prone to diabetes and hypertension. Such data reinforce the need to monitor the risk indicators as a preventive measure and early detection of some cardiometabolic diseases.